EVALUATION OF THE EXTRACULICULAR DEVELOPMENT PROGRAM OF VOLYBALL IN JUNIOR HIGH SCHOOL - Siswantoro; Moch Asmawi; James Tangkudung (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2021)
The purpose of this study was to find out the volleyball extracurricular development program in Tambun Utara sub-district using the CIPP eva-luation model (Context, Input, Process and Product). By using the CIPP method, which was presented by Daniel L. Stuflebeam, it is an evaluation of the Context discussion on the background of the program and the purpose of the coaching program. Input Evaluation is a discussion of the acceptance of athletes, coaches, funds, facilities and infrastructure. Process Evaluation, discussion on the implementation of training, consumption / nutrition, coordination and communication programs. Product evaluation, which is about the results of the guided program achievement which is obtained in the volleyball extracurricular program development. The results of this study were obtained from the results of interviews, observations and documentation studies obtained by the researchers that the volleyball extracurricular training program in Tambun North District Public Middle School had carried out the processes and procedures of sports achievement development programs in general. However, the implementation is constrained by funding, training facilities and infrastructure as well as other facilities that can support the training program. The importance of communication and coordination of sports stakeholders has not run as expected in seeking donors both local and private government.